The Plight of Foreign Workers in Japan: Their Stories Speak for Themselves - Zhang, Rong; McCornac, Dennis (Border Crossing, 2022)
Japan’s demographic changes over the past decades have prompted a sea change in immigration policy. Once such effect has been the influx of foreign labor to address labor shortages in various sectors of the economy. The purpose of this paper is to examine the recent situation of foreign workers in Japan who have been impacted by these immigration policies, particularly considering the coronavirus pandemic. We present the results of in-depth interviews with such individuals to provide insight into their working and living conditions. We conclude that to date, the new immigration system has failed to live up to expectations, and if Japan wants to accept more foreign workers to boost its economy and realize faster progress in globalization, more efforts need to be made at both the national and local levels.